2020
DOI: 10.3390/ijerph17207690
|View full text |Cite
|
Sign up to set email alerts
|

Citation Network Analysis of the Novel Coronavirus Disease 2019 (COVID-19)

Abstract: Background: The first outbreaks of the new coronavirus disease, named COVID-19, occurred at the end of December 2019. This disease spread quickly around the world, with the United States, Brazil and Mexico being the countries the most severely affected. This study aims to analyze the relationship between different publications and their authors through citation networks, as well as to identify the research areas and determine which publication has been the most cited. Methods: The search for publications was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 70 publications
0
34
0
1
Order By: Relevance
“…Top authors with the largest publications on COVID-19 were Wang Y. (0.55%), Mahase E (0.47%) and Li Y (0.43%) [10]. In our study, Dhama K. had the highest number of publications (n=23, 0.83%).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Top authors with the largest publications on COVID-19 were Wang Y. (0.55%), Mahase E (0.47%) and Li Y (0.43%) [10]. In our study, Dhama K. had the highest number of publications (n=23, 0.83%).…”
Section: Discussionmentioning
confidence: 48%
“…The most productive countries in our study were the USA, China, India, England and Italy. It was previously reported that USA, China and Italy were the countries with the highest publication rates [10]. In a study, according to publications in relation to confirmed COVID-19 cases correlated deaths and total population size, the USA were leading with the highest number of both COVID-19 cases as well as related publications [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These programs offer a much more detailed analysis when creating citation networks compared to other databases such as Web of Science or Scopus [ 13 ]. In addition, for the methodology, we based ours on other studies of citation networks carried out by our research team [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these functions make it possible for a complete analysis and study of the research on the field of study to be conducted. The methodology was based on other citation network studies carried out by our research team [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%